Intraspecific trait variation of woody species reduced in a savanna community, southwest China - Lubing Liu (Plant Diversity, 2022)
Plants deploy various ecological strategies in response to environmental heterogeneity. In many forest ecosystems, plants have been reported to have notable inter- and intra-specific trait variation, as well as clear phylogenetic signals, indicating that these species possess a degree of phenotypic plasticity to cope with habitat variation in the community. Savanna communities, however, grow in an open canopy structure and exhibit little species diversification, likely as a result of strong environmental stress. In this study, we hypothesized that the phylogenetic signals of savanna species would be weak, the intraspecific trait variation (ITV) would be low, and the contribution of intraspecific variation to total trait variance would be reduced, owing to low species richness, multiple stresses and relatively homogenous community structure. To test these hypotheses, we sampled dominant woody species in a dry-hot savanna in southwestern China, focusing on leaf traits related to adaptability of plants to harsh conditions (year-round intense radiation, low soil fertility and seasonal droughts). We found weak phylogenetic signals in leaf traits and low ITV (at both individual and canopy-layer levels). Intraspecific variation (including leaf-, layer- and individual-scales) contributed little to the total trait variance, whereas interspecific variation and variation in leaf phenology explained substantial variance. Our study suggests that intraspecific trait variation is reduced in savanna community. Furthermore, our findings indicate that classifying species by leaf phenology may help better understand how species coexist under similar habitats with strong stresses.